A Public Health Centre as Means of Preventive Health Service Facility - Burky, Vicky Anandi (Journal of Asian-african Focus in Health, 2023)
This article discusses a public health centre, which is a health service facility that organizes public health efforts and first-level individual health efforts, with a greater emphasis on promotive and preventive efforts, to achieve the highest public health status in its working area. The purpose of PKPA in Puskesmas is to increase the understanding of prospective pharmacists about the roles, functions, positions and responsibilities of pharmacists in pharmaceutical services, equip prospective pharmacists to have insight, knowledge, skills and practical experience to do pharmaceutical work, provide opportunities for prospective pharmacists to see and learn strategies and activities that can be carried out in the context of developing pharmaceutical practice, preparing prospective pharmacists to enter the world of work as professional pharmaceutical personnel, and providing a real picture of the problems of pharmaceutical work.